Implementasi Program Kerja Mahasiswa KKN dalam Peningkatan Kualitas Hidup Masyarakat Desa Perteguhen - Silvia Tabah Hati; Nabila Khairunnisa; Nia Safira Ramadhanty Pane; Cindy Alya Tantri (BADAN PENERBIT STIEPARI PRESS, 2025)
Students from Universitas Islam Negeri Sumatera Utara (UINSU) carried out a Community Service Program (KKN) in Perteguhen Village, Simpang Empat Subdistrict, Karo Regency. This program was held from July 30 to September 1, 2025. For more than a month, the students organized various activities, which were divided into major programs, weekly activities, and daily routines. The main purpose of this KKN program was to give students the opportunity to learn directly from the community while also helping to explore and develop the village’s potential. In this way, students not only gained theoretical knowledge at the university but also practical experience by engaging with the daily lives of the villagers. The implementation began with a field survey to better understand the condition of the village, followed by planning programs that matched the needs of the community. All activities were carried out with the support of the village head and local residents, creating a sense of closeness and togetherness. Some of the major programs included helping the community with activities that supported the improvement of the local economy, exploring local potential, and organizing social and religious programs to foster peace and harmony. In addition, students also worked with elementary school children by providing tutoring sessions and Qur’an lessons, giving them extra support both in academics and religious education. Through this KKN program, it is hoped that the people of Perteguhen Village can directly benefit in the areas of education, social life, and the economy. For the students, this experience served as a valuable opportunity to broaden their knowledge, build empathy, and strengthen their sense of responsibility. The presence of UINSU students in Perteguhen Village is expected to leave a positive impact by creating a more peaceful, united, and prosperous community.